Continuing dental education (CDE) programs: Are dentists keeping themselves updated? - Ramandeep S. Gambhir; Umang Jagga; Rina Singh; Ramandeep Kaur; Garish Kumar; Aanchal Gupta (Journal of Education and Health Promotion)
Dentistry is evolving at a rapid pace and continuing dental education helps a dental professional provide the latest care to the patients by using the most recent methods, skills, and technologies. Therefore, the present study was conducted to assess the perception, participation, and obstacles of private dental practitioners toward participation in continuing dental education (CDE) programs in India. A descriptive cross-sectional study was conducted among private dental practitioners in Tricity. Systematic random sampling methodology was used to select the study subjects and a total of 426 subjects comprised the study population. Data were collected through a self-constructed three-part questionnaire which included demographic information, preferences of subjects toward CDE programs, and various barriers limiting participation. Statistical analysis was done using Chi-square test and multiples logistic regression analysis. Majority of the subjects in the study were males (260, 61%) and 44.1% (188) of the subjects were postgraduates. Only 38.6% (164) of subjects said that they were regularly attending CDE programs and 84.2% (358) of subjects showed interest in CDE programs related to dental implants. A vast majority of subjects (305, 71.7%) said that they only attend CDE programs when the speaker is a renowned person. Shortage of time (257, 60.4%) and high cost/fee (249, 58.6%) of the CDE program were the main barriers that prevented the subjects from attending CDE programs. Postgraduate degree (odds ratio [OR]: 2.15, P = 0.023) and affiliation with an institution (OR: 2.46, P = 0.032) were significant factors contributing toward participation in CDE programs. More than half of the study subjects were not regularly participating in CDE programs. CDE organizers and dental associations should address the mentioned issues to ensure maximum participations of dental professionals in future programs.